Pengembangan Media Pembelajaran Permainan Uno Card pada IPAS Materi Rangka, Sendi, dan Otot Untuk Siswa Kelas VI Sekolah Dasar: (Development of Uno Card Game Learning Media for Science and Social Studies (IPAS) on Skeleton, Joints, and Muscles for Grade VI Elementary School Students) - Fara, Amalia; Filia Prima Artharina; Diana Endah Handayani (BIODIK, 2026)
The Merdeka Curriculum emphasizes student-centered learning; however, Natural and Social Sciences (IPAS) topics regarding the skeletal system, joints, and muscles often pose a challenge for students due to their complexity, requiring strong conceptual understanding and extensive memorization. Observations at SD Negeri Panohan and SD Negeri Sambongpayak revealed that students still struggle to comprehend these materials despite the use of visual aids such as images and torsos. This research focuses on the development and validation of an Uno Card-based learning tool for sixth-grade IPAS materials. Utilizing the Research and Development (R&D) method with an ADDIE procedural design, the study evaluates the media's effectiveness in terms of feasibility and teacher-student practicality. Data collection instruments included interview guides, observation sheets, as well as expert validation questionnaires and user response scales (teachers and students). The research data indicate that the developed Uno Card media meets the "highly feasible" criteria, with media expert validation reaching an average of 97%—covering media feasibility aspects (relevance, teacher capability, ease of use, availability, and usefulness) and graphic feasibility aspects (size, design, and content). Material expert validation also fell into the "valid without revision" category with an average percentage of 95,7%, as the content was deemed aligned with IPAS learning objectives and current scientific developments. The level of practicality based on teacher responses reached 98.5% and 97.1%, while student responses were 90.43% and 90.32%, categorized as "highly practical." Furthermore, the media was considered easy to use in learning activities, with card sizes and shapes appropriate for the characteristics of elementary school students. Drawing from the analyzed data, the Uno Card game media is feasible and highly practical to be utilized as a supporting tool for learning IPAS material on the skeletal system, joints, and muscles in elementary schools. Absrtak. Kurikulum Merdeka menekankan pembelajaran yang berpusat pada siswa, namun materi Ilmu Pengetahuan Alam dan Sosial (IPAS) mengenai rangka, sendi, dan otot seringkali menjadi tantangan bagi siswa karena kompleksitasnya yang membutuhkan pemahaman konseptual kuat dan bersifat hafalan. Hasil observasi di SD Negeri Panohan dan SD Negeri Sambongpayak menunjukkan siswa masih kesulitan memahami materi tersebut meskipun telah menggunakan media gambar maupun torso. Tujuan utama penelitian ini untuk menghasilkan media pembelajaran permainan Uno Card pada materi rangka, sendi, dan otot serta menguji kelayakan dan kepraktisannya untuk siswa kelas VI Sekolah Dasar. Penelitian ini menerapkan metode Research and Development (R&D) melalui prosedur pengembangan ADDIE (Analyze, Design, Develop, Implementation, Evaluation). Instrumen pengumpulan data meliputi pedoman wawancara, lembar observasi, serta angket validasi ahli dan respon pengguna (guru dan siswa). Data penelitian menunjukkan bahwa media Uno Card yang dikembangkan termasuk kriteria sangat layak dengan perolehan persentase validasi ahli media mencapai rata-rata 97% dengan aspek penilaian aspek kelayakan media (relevansi, kemampuan guru, kemudahan pengguna, ketersediaan, kebermanfaatan) dan aspek kelayakan kegrafikan (ukuran, desain, dan isi media pembelajaran), serta validasi ahli materi juga masuk kategori valid tanpa revisi dengan persentase rata-rata 96% dan materi pada media uno card dinilai sesuai dengan capaian pembelajaran IPAS dan sesuai dengan perkembangan ilmu pengetahuan yang baru. Tingkat kepraktisan media berdasarkan respon guru mencapai 98,5% dan 97,1% dan respon siswa sebesar 90,43% dan 90,47%, dikategorikan sangat praktis, serta media ini dinilai mudah digunakan dalam kegiatan pembelajaran, ukuran dan bentuk kartu sesuai dengan karakteristik siswa SD. Dengan memperhatikan hasil tersebut, peneliti menyimpulkan bahwa media permainan Uno Card layak dan sangat praktis dimanfaatkan sebagai sarana penunjang pembelajaran IPAS materi rangka, sendi, dan otot di Sekolah Dasar. Kata kunci: Uno Card, Media Pembelajaran, IPAS, Sistem Gerak, Sekolah Dasar.